1997
DOI: 10.1111/1523-1747.ep12335315
|View full text |Cite
|
Sign up to set email alerts
|

Missense Mutations in Keratin 17 Cause Either Pachyonychia Congenita Type 2 or a Phenotype Resembling Steatocystoma Multiplex

Abstract: Pachyonychia congenita (PC) is a group of autosomal dominant ectodermal dysplasias in which the main phenotypic characteristic is hypertrophic nail dystrophy. In the Jackson-Lawler form (PC-2), pachyonychia is accompanied by multiple pilosebaceous cysts, natal teeth, and hair abnormalities. By direct sequencing of genomic PCR products, we report heterozygous K17 missense mutations in the same conserved protein motif in a further five PC-2 families (K17 N92S in one familial and three sporadic cases; K17 Y98D in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(100 citation statements)
references
References 15 publications
6
93
0
1
Order By: Relevance
“…For example, the K6/K16 pair is expressed in nails, palm and sole skin, the hair follicle, and oral mucosa, which are all affected in the Jadassohn-Lewandowsky form. All mutations reported to date lie in the helix initiation LA peptide (Bowden et al, 1995;McLean et al, 1995;Smith et al, 1997). In one family, affected individuals have a three-base-pair deletion within the helix initiation peptide of K6a which removes a highly conserved asparagine residue (Bowden et al, 1995); this K6 mutation is identical to the K4 mutation reported in two families with white sponge nevus .…”
Section: (B) Skin Disorders Associated With Keratin Mutationsmentioning
confidence: 85%
See 1 more Smart Citation
“…For example, the K6/K16 pair is expressed in nails, palm and sole skin, the hair follicle, and oral mucosa, which are all affected in the Jadassohn-Lewandowsky form. All mutations reported to date lie in the helix initiation LA peptide (Bowden et al, 1995;McLean et al, 1995;Smith et al, 1997). In one family, affected individuals have a three-base-pair deletion within the helix initiation peptide of K6a which removes a highly conserved asparagine residue (Bowden et al, 1995); this K6 mutation is identical to the K4 mutation reported in two families with white sponge nevus .…”
Section: (B) Skin Disorders Associated With Keratin Mutationsmentioning
confidence: 85%
“…In one family, affected individuals have a three-base-pair deletion within the helix initiation peptide of K6a which removes a highly conserved asparagine residue (Bowden et al, 1995); this K6 mutation is identical to the K4 mutation reported in two families with white sponge nevus . Other forms of non-epidermolytic PPK resulting from mutations in K16 and K17 have been reported that have only very mild nail abnormalities (Shamsher et al, 1995;Smith et al, 1997 (Ku et al, 1997).…”
Section: (B) Skin Disorders Associated With Keratin Mutationsmentioning
confidence: 99%
“…This entity is characterized by overcurvated and thickened nails, PPK, hyperkeratosis of knees and elbows and tiny cutaneous horns over different skin areas. Although pachyonychia congenita type 2 has been associated with mutations of K17 [12]and nail involvement may be of late onset [13], this syndrome is not likely to account for the pathologic findings in our case.…”
Section: Discussionmentioning
confidence: 86%
“…Smith FJD have reported heterozygous missense mutations in K17(N 92 H and R 94 H) in two families who were diagnosed as steatocystoma multiplex [10].…”
Section: Discussionmentioning
confidence: 99%